Travel as Relationship Therapy: Examining the Effect of Vacation Satisfaction Applied to the Investment Model. (September 2016) - Durko, Angela M.; Petrick, James F.
As adults continue to work longer and take less vacation days, relationship dynamics are changing to accommodate individuals' responsibilities to career, family life, and self. Thus, the current study sought to understand how vacation satisfaction may enhance relationship commitment and possibly build stronger relationships and lessen the chance of relationship termination for adult couples. To do so, the current research applied the concept of vacation satisfaction to the Investment Model with the goal of better understanding the antecedents to relationship satisfaction and commitment. Results revealed that relationship satisfaction and quality of alternatives are good predictors of relationship commitment and that satisfaction with vacations assists the investment model in explaining couples' relationship commitment. From a practical standpoint, results revealed that tourism suppliers could use this information to promote travel as a means for strengthening relationships.